(untitled) (Colloquia Comparativa Litterarum, 2025)
A clown travels through times and identities. A personage is handed over to different creators and audiences. A voice changes its purpose. This article observes the metamorphoses of Pierrot from Commedia dell’arte through the romantic malheureux, the decadent Dandy to the perpetual loser and peace-seeker of the turn of the century, following the works of three authors: Giraud, Hartleben, and Schönberg. When and where is this journey going to end? – We don’t know.